Painters in the Splendor of Tunja: Naming Unrecognized Artists to Bring them out of Anonymity (XVI and XVII centuries) - Vargas Murcia, Laura Liliana (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Tunja has stood out as one of the riches cities of New Kingdom of Granada, regarding the presence of painting in the last decades of the XVI century and the first half of the XVIIth. Its painters were of importance not only in this city but in the rest of the Province as well, with the churches and museums of Boyacá containing images that were essential elements in the indoctrination of indigenous communities. Civil mural works of art in Tunja have been an object of study mostly for their interpretation, and less regarding the identities of their makers. As far as easel painting, Angelino Medoro eclipsed the names of other artists who contributed to making Tunja one the the most representative cities of the Mannerism and Renaissance of Hispanic America. This article presents the names of some of the active painters of this period, their lives and production, seeking the recognition of these characters, whose names have been brought out of anonymity in the latest years. The starting point for the information search was the research of Magdalena Corradine Mora on the inhabitants of Tunja in the first decades of the XVII century, and the search for information in the Boyacá Regional Historical Archive. In calling attention upon these artists, we hope that, in the future, the identification of their works may be initiated as well as the research, conservation and dissemination of these works, due to the fact that this heritage is not always in ideal conditions, nor is it perceived and valued as is deserved.